Family waqf deserves a better deal - Sadique, Muhammad Abdurrahman (IIUM Press, 2014)
This write-up attempts to shed light on the hostile treatment of family waqf under the colonial imposition of the English notion of ‘charity,’ which excludes family trust or waqf from the category of charity. Many Muslim countries adopted this view without much scrutiny. It is necessary to remind ourselves the support this waqf finds in the Qur’anic injunctions and Prophetic pronouncements and what benefits its revival should bring to the Ummah.